Do genetic recombination and gene density shape the pattern of DNA elimination in rice long terminal repeat retrotransposons? - Tian, Zhixi; Rizzon, Carene; Du, Jianchang; Zhu, Liucun; Bennetzen, Jeffrey L.; Jackson, Scott A.; Gaut, Brandon S.; Ma, Jianxin (Genome Research, 2009)
In flowering plants, the accumulation of small deletions through unequal homologous recombination (UR) and illegitimate recombination (IR) is proposed to be the major process counteracting genome expansion, which is caused primarily by the periodic amplification of long terminal repeat retrotransposons (LTR-RTs). However, the full suite of evolutionary forces that govern the gain or loss of transposable elements (TEs) and their distribution within a genome remains unclear. Here, we investigated the distribution and structural variation of LTR-RTs in relation to the rates of local genetic recombination (GR) and gene densities in the rice (Oryza sativa) genome. Our data revealed a positive correlation between GR rates and gene densities and negative correlations between LTR-RT densities and both GR and gene densities. The data also indicate a tendency for LTR-RT elements and fragments to be shorter in regions with higher GR rates; the size reduction of LTR-RTs appears to be achieved primarily through solo LTR formation by UR. Comparison of indica and japonica rice revealed patterns and frequencies of LTR-RT gain and loss within different evolutionary timeframes. Different LTR-RT families exhibited variable distribution patterns and structural changes, but overall LTR-RT compositions and genes were organized according to the GR gradients of the genome. Further investigation of non-LTR-RTs and DNA transposons revealed a negative correlation between gene densities and the abundance of DNA transposons and a weak correlation between GR rates and the abundance of long interspersed nuclear elements (LINEs)/short interspersed nuclear elements (SINEs). Together, these observations suggest that GR and gene density play important roles in shaping the dynamic structure of the rice genome.